2017
DOI: 10.1002/jnr.24125
|View full text |Cite
|
Sign up to set email alerts
|

Different resuscitation strategies and novel pharmacologic treatment with valproic acid in traumatic brain injury

Abstract: Traumatic brain injury (TBI) is a leading cause of death in young adults, and effective treatment strategies have the potential to save many lives. TBI results in coagulopathy, endothelial dysfunction, inflammation, cell death, and impaired epigenetic homeostasis, ultimately leading to morbidity and/or mortality. Commonly used resuscitation fluids such as crystalloids or colloids have several disadvantages, and might even be harmful when administered in large quantities. There is a need for next-generation tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 106 publications
(136 reference statements)
1
7
0
Order By: Relevance
“…In clinically realistic large animal models, VPA has been shown to improve survival from otherwise lethal injuries (26), reduce brain lesion size and swelling (9, 27), and improve neurologic recovery (10,27). Recent evidence has shown that these clinical outcomes may be attributed to VPA's ability to alter gene expression and cell physiology (15,16,23,28,29), thereby creating a pro-survival phenotype (30)(31)(32). We have previously demonstrated that resuscitation with combined FFPþVPA resulted in a significant reduction of both brain lesion size and swelling compared with FFP alone (12).…”
Section: Discussionmentioning
confidence: 99%
“…In clinically realistic large animal models, VPA has been shown to improve survival from otherwise lethal injuries (26), reduce brain lesion size and swelling (9, 27), and improve neurologic recovery (10,27). Recent evidence has shown that these clinical outcomes may be attributed to VPA's ability to alter gene expression and cell physiology (15,16,23,28,29), thereby creating a pro-survival phenotype (30)(31)(32). We have previously demonstrated that resuscitation with combined FFPþVPA resulted in a significant reduction of both brain lesion size and swelling compared with FFP alone (12).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive NMDA receptor activity induced by high levels of extracellular glutamate increases the risk of encephalopathy and reduces seizure threshold. Hyperammonemia may also lead to impairment in the membrane aquaporin system and brain electrolyte homeostasis, all of which may result in neuronal toxicity and cerebral edema in astrocytes [53].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to synthetic colloids, animals resuscitated with 0.9% sodium chloride or LRS required larger volumes of fluid to reach and maintain hemodynamic endpoints, developed progressive acidosis, and were volume-dependent to maintain MAP and CPP (19,20). Other animal model studies found that resuscitation from hemorrhagic shock with isotonic crystalloid solutions was associated with lower CPP, higher ICP, lower MAP, higher glutamate-mediated excitotoxic secondary brain injury and increased mitochondrial dysfunction, lower brain tissue oxygenation, more brain edema, larger brain lesion size, upregulation of inflammatory pathway genes, increased activation of coagulation, anticoagulation, and endothelial systems, greater degree of neurologic impairment, and markedly slower rate of neurologic recovery when compared to plasma products, regardless of the type of TBI model studied (17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Isotonic Crystalloidsmentioning
confidence: 92%
“…Modern damage control resuscitation guidelines for hemorrhaging patients recommend avoidance of crystalloid fluids in favor of early initiation of a 1:1:1 ratio-based transfusion strategy using packed red blood cells, plasma, and platelets (15). This strategy may mitigate hemodilution, hemostatic derangements, brain edema, and inflammation associated with large volume crystalloid infusion and worsening of uncontrolled hemorrhage (9,(15)(16)(17). In a pig model of TBI and uncontrolled hemorrhage, 100% of pigs died in less than one hour when aggressively resuscitated with isotonic crystalloid solution to a MAP of 80 mmHg, while 50% of pigs that were allowed to remain hypotensive with no resuscitation for one hour survived and went on to have cerebral blood flow return to normal in the second hour following surgical hemostasis and resuscitation with shed blood (18).…”
Section: Isotonic Crystalloidsmentioning
confidence: 99%